A single-stage Stirling-type pulse tube cryocooler achieving 1080 W at 77 K with four cold fingers driven by one linear compressor. (March 2020) - Dang, Haizheng; Li, Jiaqi; Zha, Rui; Tan, Jun; Zhang, Tao; Zhao, Bangjian; Zhao, Yongjiang; Li, Ning; Tan, Han; Xue, Renjun
Highlights: A single-stage Stirling-type pulse tube cryocooler achieves 1080 W at 77 K. Four pulse tube cold fingers are driven by one linear compressor. Flow characteristics in both pulse tubes and regenerators are studied. Interactions and controlling among the four cold fingers are analyzed. The high capacity cryocooler achieves a relative Carnot efficiency of 16%. Abstract: This paper presents the design, optimization and experimental verification of a high-capacity single-stage Stirling-type pulse tube cryocooler (SPTC) with four cold fingers driven by only one linear compressor. The flow characteristics in both pulse tubes and regenerators are studied with the aid of CFD, and the effects of flow straighteners and operating parameters on the cooling performance analyzed in detail. The interactions and performance controlling among the four cold fingers are emphasized. The developed SPTC can experimentally achieve a cooling capacity of 1080 W at 77 K with a relative Carnot efficiency of 16%, which suggests a good alternative for cooling large-scale high-Tc superconducting (HTS) facilities such as HTS cables.